1988
DOI: 10.1002/ijch.198800026
|View full text |Cite
|
Sign up to set email alerts
|

Formation Dynamics, Decay Kinetics, and Singlet–Triplet Splitting of the (Bacteriochlorophyll Dimer)+ (Bacteriopheophytin) Radical Pair in Bacterial Photosynthesis

Abstract: We explore the interrelationship between (i) the kinetic data for the primary electron transfer (ET) from the excited singlet state (1P*) of the bacteriochlorophyll dimer (P) to bacteriopheophytin (H) in the reaction centers (RCs) of purple photosynthetic bacteria and (ii) the energetics and dynamics of the primary radical pair, P+H, i.e., its singlet‐triplet splitting rate, J, and triplet recombination rate, kT. We present a critical scrutiny of the ET mechanisms with regard to the role of the accessory bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…A shift of 1 (P + H A -) of at least 10 -2 cm -1 ≈ 100 G was estimated. 2,10,12,13,16 This is much larger than the experimentally observed value of J. Two possibilities to resolve this discrepancy when assuming superexchange charge separation were discussed: (i) a fortuitous compensation of the shift of 1 (P + H A -) by an equivalently large shift of 3 (P + H A -) in the same direction; however, the maximum values of the triplet shift calculated with a more refined theoretical treatment 14,98 including the interaction with all vibronic states are not large enough to compensate the expected large values of the singlet shift; (ii) a fast decrease of the coupling between P and H A due to some conformational relaxation after charge separation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A shift of 1 (P + H A -) of at least 10 -2 cm -1 ≈ 100 G was estimated. 2,10,12,13,16 This is much larger than the experimentally observed value of J. Two possibilities to resolve this discrepancy when assuming superexchange charge separation were discussed: (i) a fortuitous compensation of the shift of 1 (P + H A -) by an equivalently large shift of 3 (P + H A -) in the same direction; however, the maximum values of the triplet shift calculated with a more refined theoretical treatment 14,98 including the interaction with all vibronic states are not large enough to compensate the expected large values of the singlet shift; (ii) a fast decrease of the coupling between P and H A due to some conformational relaxation after charge separation.…”
Section: Discussionmentioning
confidence: 99%
“…sphaeroides. 10,16 This is larger by a factor of 20 than the electronic coupling V T between 3 (P + H A -) and 3 P*; see below. Triplet recombination from P + H A -is near the activationless case; triplet recombination from P + B A -, on the other hand, has a larger freeenergy gap, but is not expected to have a larger reorganization energy.…”
Section: The Energetics Of the Radical Pairs P + H A -And P + B A -mentioning
confidence: 93%
“…[46] These data were taken as an important indication for a superexchange ET as the primary charge-separation process in photosynthesis: the electron should not be transferred step by step between neighbouring chromophores as was expected from conventional Marcus- [49] Even if the superexchange model seemed to be convincingly supported by experiments and theory, [30,50,51] a number of unsolved questions or contradictory results had to be considered: Studies on the initial reaction dynamics and intended to develop a unifying view of the reaction centre, had difficulties to reconcile a superexchange forward reaction with recombination dynamics. [51][52][53][54][55] Inspecting the data of Martin and Breton, R. Marcus found that these data would not exclude the existence of an intermediate P + B A À even with a relatively long lifetime of up to 1 ps. [52] Simulations on the energetics of intermediates that considered the published structure of the reaction centre and polar molecules in the vicinity of the electron carriers indicated that the energy of intermediate P…”
Section: The Primary Reaction Stepsmentioning
confidence: 99%
“…There was no generally accepted experimental evidence of an intermediate electron-carrying state B- (16)(17)(18)(19)(20)(21)(22)(23). The postulated direct electron transfer from P to H imposed numerous difficulties on the theoretical description of the charge-transfer process (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) …”
mentioning
confidence: 99%